Effects of cultivation system and temperature on methane emissions, water consumption and methane-oxidizer bacteria communities in paddy soil - Fazli, Pardis (2014)
Methane (CH4) is a potent greenhouse gas with a global warming potential of 25 times more than CO2. Paddy fields are important sources of methane and contribute in approximately 15–20% of the annual global methane efflux. Methanogens and methanotrophs are two microbial communities contribute in the biogeochemical methane cycle in soil by producing and oxidizing the methane respectively. In fact, the total methane emission from rice soil is the balance between methanogens and methanotrophs activities. Methane emission rate could be affected by several factors such as irrigation pattern, fertilizer type, soil organic matter and soil temperature. Between them, soil temperature is a determining factor which deserves to be investigated. Also, cultivation systems can affect the methane emission by their different water management and practices. One of the cultivation methods is the System of Rice Intensification (SRI) which includes Original SRI and blong-Triangular SRI. Therefore, this study was performed with the main aim of introducing a sustainable rice production system with less contribution to global warming and more productivity. Therefore, the effect of soil temperature and different cultivation systems on the methane emission rate from rice soil was studied. In addition, identification of methane-oxidizer bacteria (MOBs) was conducted in two rounds. Static chamber method has been applied to evaluate the influence of two SRI methods and conventional method on methane emission. As a result,conventional method showed the highest total methane flux with emitting of 26.4 g CH4 m-2 compared to original SRI treatments and triangular pattern with 7.7 g CH4 m-2 and 8.9 g CH4 m-2 respectively. The pattern of water management was the most influencing factor led to lower methane emission in SRI treatments. SRI treatments produced higher yield than the conventional method so that original SRI produced 6.98 and 7.00 ton ha-1, oblong-triangular SRI yielded 7.08 and 7.01 ton ha-1 at first and second round respectively. On the other hand, conventional method presented 6.74 and 6.80 ton ha-1 grain yield at first and second round respectively. Besides, more than 40% water saving was observed in original and oblong-triangular SRIs while higher water productivity including 7.93 and 7.86 kg ha-1 mm-1 were recorded in these cultivation systems compared to conventional method with 4.49 kg ha-1 mm- 1. This could be a promising result toward a sustainable rice production. Moreover, soil temperature showed positive correlation with methane emission both in daily measurements (0.768) and during rice growth season (0.528). However,factors such as water management and plant age decreased this correlation during growth season. Furthermore, this experiment applied PCR-DGGE to detect MOBs within the rice soil from two depths between 0 to 5 and 5 to10 cm in different rice growth stages and cultivation systems. Consequently, several MOBs from type I and type II have been identified. However, type I was detected at 0-5 cm depth and drained condition rather than 5-10 cm depth and flooding condition. Both systems of rice intensification (SRI treatments) were revealed to provide stimulating condition for MOBs (Esp. Type I) compared to conventional method because of aerating the soil alternatively. Besides, SRIs showed higher diversity of MOBs in comparison with Conventional method. SRIs reduced the methane emission by affecting the MOBs' communities. In this regard, SRIs provided favourable condition for type I MOBs to be active and oxidize more portion of produced methane in the soil before being released into the atmosphere. Consequently, SRIs could succeed in methane emission mitigation from paddy soil while they produced more grain yield and represented less water usage. As a conclusion, this study can introduce SRIs as green cultivation systems for a sustainable rice production.